Cultural Heritage Study of Avanos, Cappadocia in Relation to its Waterfront - Berkmen, Hulya (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
When historical development and identity of settlements is analyzed functionally, two very different formations stand out. One concerns man-made elements and their functions, which have been developed and enriched over time, and are present in every settlement. The second concerns elements particular to a settlement that determine its role, history, and identity, and dictate its functions. The present study addresses water as the reason for the existence of certain settlements. The region of Cappadocia is located on the banks of Kizilirmak River, or Red River, which is the longest river in the second largest basin in Turkey. While the Kizilirmak has played an active role in both the physical formation and cultural structure of the region, it has had a greater effect on the identity, development, and economic structure of the settlement of Avanos, located on the river's banks. Here, the water element includes not only the Red River, but all water resources, such as streams that feed the river and ground water. The relationship with water and its effects on the historical process and identity of Avanos is discussed, with an emphasis on the tourism economy and planning issues of the region.
Keywords: Waterfront settlements; cultural heritage; tourism economy; Architecture